Physical Maps of Autographa californica and Rachiplusia ou Nuclear Polyhedrosis Virus Recombinants - Summers, Max D. (1980)
TN-368 cells were infected simultaneously with the closely related Autographa california (AcMNPV) and Rachiplusia ou (RoMNPV) nuclear polyhedrosis viruses. Progeny viral isolates were plaque purified, and their DNAs were analyzed with restriction endonucleases. Of 100 randomly cloned plaques, 7 were AcMNPV and RoMNPV recombinants, 5 were RoMNPV, and 88 were AcMNPV. The recombinants contained DNA sequences derived from both parental genomes. By comparing the restriction cleavage patterns of parental and recombinant DNAs, the crossover sites were mapped. A single double crossover was detected in each of the seven recombinant genomes. In addition, six of the seven recombinants revealed a crossover site mapping between 78 and 89% of the genome. The structural polypeptides of the seven recombinants and two parental viruses were analyzed by polyacrylamide gel electrophoresis, and their polyhedrins were identified by tryptic peptide mapping. An analysis of the segregation of three enveloped nucleocapsid proteins and of the polyhedrins among the recombinants located the DNA sequences coding for AcMNPV structural polypeptides with molecular weights of 37,000 (a capsid polypeptide), 56,000, and 90,000 and the RoMNPV structural polypeptides with molecular weights of 36,000 (a capsid polypeptide), 56,000, and 91,000. The AcMNPV and RoMNPV polypeptides of molecular weights 37,000 and 36,000, respectively, mapped within 78 to 89% or 1 to 29%, the polypeptides of molecular weights 55,000 and 56,000 mapped within 78 to 29%, and the polypeptides of molecular weights 90,000 and 91,000 mapped within 19 to 56% of the genome. The region of the parental DNAs that codes for polyhedrin was located within 70 to 89% of the genome.